Plan de negocio para la exportación de palta fresca (Persea Americana Millar) con destino a EE.UU en la Empresa Food Export Norte S.A.C 2016 - Huarcaya Moreno, Stefany del Carmen (2016)
This research was carried out in the exporting company Food Export Norte SAC of the Lambayeque Region in the year 2016, in which the representatives of the Food Export Norte SAC, where the managers of the companies of Avocado Hass of the department of Lambayeque and experts in the matter of The Northern Region Macro participed. The Problem was posed as follows: Which marketing tool will allow the export of fresh avocado to the United States at the company Food Export North SAC?, the main objective was to develop a business plan for the export of fresh Avocado with destination to The United States at the company Food Export Norte SAC, for which a diagnosis was made of the current state of export of fresh avocado to The United States. The research was non-experimental, descriptive, correlational and cross- sectional where the study population consisted of four from Food Export Norte SAC, 4 companies exporting fresh avocado Lambayecanas and three Specialists in the export of fresh avocado. Likewise, instruments such as seven interview guide and four questionnaires validated by experts were used for data collection. Finally, it has been concluded that The United States, is a country with great potential importing Peruvian avocado, and that the opportunities can be exploited to the extent that supply is properly organized, complying with the requirements established for its export how to meet quality standards.